PERAN GURU DAN AKHLAK SISWA DALAM PEMBELAJARAN: Perspektif Syekh Az-Zarnuji Kitab Ta’lim Muta’allim - Wiwin Candra; Ahmad Dibul Amda; Bariyanto Bariyanto (Institut PTIQ Jakarta, 2020)
Morality is a trait firmly embedded in the soul which is seen in outward actions that are done easily without the need for more thought, and that have become a habit. Morality is prioritized in daily life, especially in teaching and learning processes, wherein students must have morals to the teacher, to knowledge, and to their peers. This study aims to elicit information about: how the teacher’s role in applying the morality of learning resting on Sheikh Az-Zarnuji’s perspective in his book Ta'lim Muta’allim. This is a library research. The results of study and analysis of Sheikh Az-Zarnuji’s book, Ta'lim Muta'allim, draw a conclusion that the teacher’s role is twofold: Sufistic and pragmatic roles. In the meantime, the morality of learning in Ta'lim Muta’allim book comprises five parts, namely: good intentions; choosing the teachers’ knowledge and study partner; respecting teachers’ knowledge; being sincere in learning perseverance and ideals; and the attitude of wara’ in learning.